Funcionarios. (UNED, 2024)
De pie de izquierda a derecha Bolívar Bolaños Calvo, Cristina Pizarro Piña, Jeannette Vargas Jiménez, Xinia Zuñiga Muñoz, Ethel Pazos Jiménez, Rodrigo Salas de la Paz, Mercedes Mesén Valverde, Patricia Rodríguez, Theodosia Mena Valverde, sentados de izquierda a derecha José Luis Torres Rodríguez, Hernán Cordero González y Carlos Benavides.